Listeria Monocytogenes: a rare cause of endophthalmitis, a case report. (2017) - Gaskell, Katherine M.; Williams, Gwyn; Grant, Kathie; Lightman, Susan; Godbole, Gauri
Highlights: First case described in England. Listeria spp. must be considered in an inflamed eye after infective gastroenteritis. Listeria spp. endogenous ophthalmitis is rare, difficult to diagnose and treat. The regimen described was successful in achieving control of intraocular infection. Control of the intraocular infection may not result in visual recovery. Abstract: Listeria monocytogenes is a known cause of gastroenteritis. Invasive disease can follow bacteremia causing meningoencephalitis, endocarditis and spontaneous miscarriages in immunocompromised patients and pregnant women respectively. We present the first case in England of endogenous endophthalmitis caused by L. monocytogenes following acute gastroenteritis in an immunocompetent host. A 50-year-old South Asian female presented with acute painful unilateral visual loss occurring shortly after an episode of self-limiting gastroenteritis. On examination, the eye was very inflamed with a hypopyon uveitis. A vitreous biopsy confirmed growth of L.monocytogenes serotype 1/2a. Diagnostic delay commonly occurs in endogenous endophthalmitis and exacerbates an already poor visual prognosis. Listeria spp. must be considered in ocular inflammation following gastroenteritis. The intraocular inflammation subsided but surgical intervention was required to remove vitreous debris and improve visual acuity.